Exploring health security trends in low-income countries using a hybrid D-CRITIC-CoCoSo and K-Means approach - Adel A. Nasser; Abed Saif Ahmed Alghawli; Salem Saleh; Amani A. K. Elsayed (Global Security: Health, Science and Policy)
This study evaluates health security trends in low-income countries (LICs) using a hybrid D-CRITIC-CoCoSo and K-means approach. Analysis of Global Health Security Index data from 2017 to 2021 reveals divergent priorities between LICs and high-income countries. LICs emphasise health system capacity and prevention, while HICs focus more on detection and compliance. Ethiopia and Uganda emerge as top performers among LICs, while conflict-affected states like Somalia. Syria and Yemen rank lowest. Temporal shifts show increased emphasis on rapid response capabilities in LICs post-COVID-19. Clustering analysis identifies distinct performance tiers, highlighting strengths and vulnerabilities across countries. Correlation analysis finds that capacity for medical countermeasures, financing, and international cooperation are strongly associated with improved health security outcomes in LICs. The findings underscore the need for context-specific strategies, sustained investment in health systems, and global cooperation to enhance health security in resource-limited settings. This comprehensive assessment provides insights to guide evidence-based policymaking and resource allocation.